PROCESSAMENTO, CARACTERIZAÇÃO E ESTUDO DE FENÔMENOS CRÍTICOS NOS SISTEMAS SUPERCONDUTORES (Er,Gd)1−xPrxBa2Cu3O7 - Lopes, Cristiano Santos (2010)
In this work we report on conductivity fluctuation measurements in polycrystalline samples of the Er1xPrxBa2Cu3O7 and Gd1xPrxBa2Cu3O7superconductor. Pr contents are 0.00, 0.05 and 0.10. Samples were prepared by the standard solid-state reaction technique and characterized by SEM, X-ray diffraction and electrical transport experiments. The samples were granular and homogeneous. The results were analyzed in terms of the temperature derivative of the resistivity and of the logarithmic temperature derivative of the conductivity, what allowed identifying power-law divergences of the conductivity. For Er1−xPrxBa2Cu3O7 samples, the results show that the transition proceeds in two stages: pairing and coherence transition. Also, our results, from the critical exponent analysis, show a two-peak splitting at pairing transition, indicating possibly a phase separation. On approaching the zero resistance state, our results show a power-law behavior that corresponds to a phase transition from paracoherent to a coherent state of the granular array. For Gd1−xPrxBa2Cu3O7 samples, it was observed that the critical temperature decreases and that the transition width increases with increasing Pr doping. Systematic measurements of fluctuation conductivity are reported and special attention is taken above the critical temperature, where Gaussian and critical regimes are observed. Below the critical temperature, on approaching the zero resistance state, our results show a power-law behavior consistent with a phase transition from a paracoherent to a coherent state of the granular array.